Extradition Agreement and Police to Police Cooperation in The Lens of Responsive Law: Perjanjian Ekstradisi dan Kerja Sama Antar Kepolisian dalam Perspektif Hukum Responsif - Fathanul Umara, Azzura (Faculty of Law Hang Tuah University, 2026)
This study examines the practice of surrendering fugitives between Indonesia and foreign countries, which is primarily conducted through two mechanisms: extradition treaties and police to police (P to P) cooperation under Interpol coordination. This duality raises fundamental questions regarding the differences in legal construction, effectiveness, and the extent to which each mechanism aligns with the principles of responsive law. The purpose of this research is to analyse the normative, procedural, and practical foundations of both mechanisms and to assess how well they reflect the characteristics of a responsive legal system as formulated by Philippe Nonet and Philip Selznick. The research employs a normative legal approach, combining doctrinal analysis of relevant laws and international agreements with theoretical interpretation of the concept of responsive law. The study focuses on provisions in extradition laws, bilateral treaties, and the principles guiding international cooperation by the Indonesian National Police through Interpol channels. The findings indicate that the extradition mechanism, with its formal legal basis and strong inter-state obligations, more closely embodies a responsive legal system by ensuring accountability, transparency, and legal certainty. In contrast, the P to P mechanism—while more flexible and efficient in practice—tends to be pragmatic and does not fully reflect the principles of legal responsiveness. Nevertheless, its flexibility and efficiency make P to P the preferred operational choice for law enforcement agencies in handling cross-border fugitive cases. In short, extradition treaty should be the default choice in an ideal situation where the clauses are applicable and P to P is the choice that can be used when the condition requires flexibility and pragmatism, especially when there is no extradition treaty that can be used as a base to extradite.